Removal of Paracetamol by Powdered Activated Carbon Synthesized From Orange Peels - İrem Konuk Akça; Rabia Köklü (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
This study aims to investigate the removal of Paracetamol active ingredient from aqueous solutions with the use of powdered activated carbon obtained by ZnCl2 activation of orange peels. Equilibrium values of initial paracetamol concentration (100-500 mg L-1), pH (2-10), adsorbent dose (10-500 mg) and contact time (5-120 minutes) parameters in the removal of paracetamol from aqueous solutions are evaluated. The adsorption mechanism of paracetamol is explained with the kinetic models. The highest correlation among Langmuir, Freundlich, Temkin, and Dubinin-Radushkevichi isotherms applied to experimental data was determined as Freundlich isotherm with R2 =0.95. Pseudo-first-order and pseudo-second-order kinetic models were applied, and it was found that the latter, whose correlation coefficient is determined as R2 =0.99, is the best model to explain paracetamol adsorption. As a result of this study, it can be seen that powdered activated carbon synthesized from orange peel is an effective adsorbent in the removal of paracetamol and can be easily applied thanks to its low cost.